Hydrogen Production from Flare Gas via Steam Methane Reforming: A Simulation-Based Approach - OSEKE, Gbenga G.; AMADI, Chisom S.; RAJI, Abubakar U. (FUDMA Journal of Engineering and Technology, 2026)
Hydrogen gas is receiving significant attention as a versatile and alternative energy carrier with the possibility of being used for different purposes in industries, including power or energy generation, chemical production, transportation, and iron and steel production, with minimal environmental impacts and concerns when produced from renewable and alternative sources. This study investigated hydrogen production from flare gas via Steam Methane Reforming (SMR) using a simulation-based approach. With Nigeria experiencing significant gas flaring challenges, the research explores converting flare gas into a valuable energy resource. Using DWSIM as the simulation tool, the SMR process was modelled under varying conditions of temperature, pressure, and steam-to-carbon (S/C) ratio. Results showed that Nigerian flare gas can achieve hydrogen yields of up to 72.9 mol% and methane conversion efficiencies exceeding 92% under optimal conditions (950°C, 5 bar, S/C = 4.0). The baseline case (850°C, 15 bar, S/C = 3.0) achieved a hydrogen yield of 68.7 mol% with 85.4% methane conversion, validating flare gas as a suitable feedstock for hydrogen production. Sensitivity analysis revealed that higher temperatures and lower pressures favoured hydrogen yield, while the optimal S/C ratio was between 2.5 and 3.5. Environmental impact analysis indicated a potential 27% reduction in CO₂ emissions compared to direct flaring, alongside elimination of unburned hydrocarbons and particulates. These findings demonstrate that flare-to-hydrogen conversion is technically feasible and environmentally beneficial, offering Nigeria a dual pathway to reduce flaring while advancing its clean energy transition.